Analysis Infiltration Waters in Various Forms of Irrigation Channels by Using Dual Reciprocity Boundary Element Method - Ana Nurhasanah; Muhammad Manaqib; Irma Fauziah (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2020)
This research discusses the inﬁltration of furrow irrigation invarious forms of irrigation channels in homogeneous soils. The governing equation of the problems is a Richard’s Equation. This equation is transformed using a set of transformation including Kirchhoff and dimensionless variables into Helmholtz modiﬁed equations. Furthermore with Dual Reciprocity Boundary Element Method (DRBEM), numerical solution of modiﬁed Helmholtz equation obtained. The proposed method is tested on problem involved inﬁltration from periodic ﬂat channels, non-ﬂat channels without impermeable and non-ﬂat channels with impermeable. The greatest value of suction potential and water content is located below the channel surface. The most water consecutively is a non-flat channel without impermeable, non-flat channel with impermeable and flat channel on Lakish Clay soils.